Biogas Production From Date Palm Fruit Waste as an Alternative Energy Source in Jigawa State, Nigeria (Journal of Environmental Bioremediation and Toxicology, 2024)
This research was conducted to produce biogas from Date Palm fruit waste, which is abundant in the study area. The Date Palm fruit waste, which acts as a substrate, was collected from the Nigerian Institute for Oil Palm Research (NIFOR) Dutse substation in Jigawa State, Nigeria. Three different anaerobic digesters, along with their corresponding control digesters, were set up for a period of forty-two (42) days. For the anaerobic digestion process, a 15-litre cylinder with a working volume was used, equipped with air-tight lids and provision for gas collection. The digesters were fabricated at the Federal University's Research Centre in Dutse and were maintained at 37 °C in the University's Botanical Garden. They were shaken manually approximately 2-3 times a day to maintain homogeneity of the contents. The result shows the highest biogas concentration at 0.5 w/w (2000 g/mL), which is 10.5 g, while the lowest biogas concentration (3.4 g) was recorded in an aerobic digester containing a 2:1 wastewater ratio with 200 mL of cow dung as slurry. On the other hand, the control anaerobic digester produced a very small amount of biogas from the respective digester, which contains only slurry and water. It is therefore recommended that date palm fruit waste be utilized for the production of biogas as a substitute for fossil fuel, in line with the United Nations Sustainable Development Goals.
Keywords: Date palm; Fruit waste; Codigestion; Biogas yield; Sustainable production